Analisis Penipuan Digital Teknik Phishing Terhadap Layanan Mobile Banking - Cut Mutia; Rayyan Firdaus (Jurnal Transformasi Bisnis Digital, 2024)
Currently, advances in Internet technology can help the banking sector run its operations better, one of which is the existence of electronic banking (e-banking), and what is popularly used by the public today is Mobile Banking services. It turns out that there are advantages as well as disadvantages, namely the dangers of digital crime. One of the attack techniques that are often carried out to threaten the security of mobile banking is phishing attacks. Phishing is a manipulation technique that tricks users into revealing the victim's data to open the data or steal the victim's identity. The literature review method, which is a method for reading and analyzing data from papers, books, articles, and videos, is used in this kind of research. The research aims to analyze phishing techniques for mobile banking services and find out the types of phishing fraud modes to maintain security in every transaction. The research results can provide information regarding important steps to prevent digital fraud.